Multi-omics integration reveals organ-specific biosynthesis of flavonoids and terpenoids in the medicinal plant Bidens alba - Wang, Zhaochu; Xu, Xinyu; Zhang, Peilan; Huang, Ye; Zhao, Chenzi; El-Kassaby, Yousry A.; Chen, Yangtao; Wang, Jing; Shi, Rong (Frontiers in Plant Science, 2025)
IntroductionBidens alba is a traditional medicinal plant valued for its antioxidant, anti-inflammatory, and antimicrobial properties, largely attributed to flavonoids and terpenoids. However, the tissue-specific distribution and regulatory mechanisms of these metabolites remain poorly understood.MethodsWe employed a combined approach of reference-guided transcriptomics and widely targeted metabolomics to investigate the biosynthesis and accumulation of flavonoids and terpenoids in four tissues (flowers, leaves, stems, and roots) of B. alba.ResultsA total of 774 flavonoids and 311 terpenoids were identified. Flavonoids were enriched in aerial tissues, while certain sesquiterpenes and triterpenes accumulated in roots. Transcriptome profiling revealed tissue-specific expression of key biosynthetic genes, including CHS, F3H, FLS, HMGR, FPPS, and GGPPS, which corresponded with metabolite patterns. Several transcription factors, such as BpMYB1, BpMYB2, and BpbHLH1, were identified as candidates regulating flavonoid biosynthesis, with BpMYB2 and BpbHLH1 showing contrasting expression between flowers and leaves. For terpenoid biosynthesis, BpTPS1, BpTPS2, and BpTPS3 were identified as putative regulators of enzymes including GPPS and DXR, with BpTPS2/3 highly expressed in flowers.DiscussionThese findings provide new insights into the transcriptional and metabolic basis of tissue-specific secondary metabolism in B. alba. The identified candidate genes and regulatory factors represent valuable targets for future functional validation and hold potential for medicinal development and molecular breeding of this species.